(untitled) (Italian Review of Legal History, 2021)
The notarial certification of financial and mercantile relations is one of the aspects of what Paolo Cammarosano has described as the «new weight of the notaries in the complex of political and social life» from the twelfth century onwards, an evolution characterised by a change in the «borders between public and private». The aim of this paper is to understand, in the concreteness of documentary production, the role of notaries in defining the modes and forms of economic relations. The analysis will focus on examples taken from documents of the 13th and 14th centuries relating to Asti and southern Piedmont. The cases presented allow a comparison between writing practices – characterised by a marked experimentation – and articulated credit relations. In this way it is possible both to understand the socio-economic dynamics that innervate one of the main municipalities of northern Italy and to highlight the functionality of certification processes in the hands of notaries, who exercised a notable role of orientation in financial and commercial relations. This analysis cannot prescind from the historiographic lines drawn by the generous magisterium of Gian Giacomo Fissore, to whom we owe decisive studies on subalpine notaries and particular attention to the notarial registers of Asti in the 13th and 14th centuries. These registers collect instrumenta concerning juridical transactions – mortgages, sales, rents – through which a network of relationships is outlined, involving the city and the territory, a large sector of central-southern Piedmont gravitating on the municipality and diocese of Asti. In particular, the cases that we will examine concern the financial activity of laymen and clergymen – covering different types of credit, from financing to the management of investments, such as deposits and commende – and the definition of give-and-take relationships, carried out both informally and through a judicial process. The attested documentary forms therefore reveal a complex system of regulation, managed by experts in judicial and economic mediation, sanctioned by notaries and capable of a widespread work of remodelling the internal dynamics of society. It is evident that the notary’s intervention defines the nodal elements of economic relations, of which he grasps the criticalities that the writing attempts to resolve by diluting the traits of uncertainty in the establishment of credit relations, constructing mechanisms of compensation and regulation, and again elaborating the ways and forms of the complex encounter between credit and politics in the case of fiscal default. A role that Rolandino effectively outlines, tabelliones vel scrinearios appellamus, eo quod sicut inventum thessaurum in scrineo reconditur ut servetur, sic merito debet omnis fides omnisque legalitas et quicquid eis in fide ac legalitate committitur per eos inviolabiliter reservari, describing a “treasure” built on fides and legalitas, inviolably preserved thanks to notarial skills. Not only that: «omnibus que [tabelliones] scripserint fides datur, nec audet quis de levi ausu temerario infringere publice quod scripserint». The fides fixed in a scripture cannot therefore be “broken”. In this perspective, a “treasure trove” is being built up through writing, framing relationships characterised by a marked dynamism and which – precisely in order to respond to their structural instability – in turn takes on dynamic traits, regulating the projection in time of obligations and commitments. The lasting functionality of potentially conflicting relationships is at stake in the deeds, since the documents notarized by the notaries do not simply sanction renegotiation but also set out the mechanisms that ensure its effectiveness in a diachronic perspective. These are articulated practices that correspond to precise competences of the notary, who, according to the widespread thirteenth-century formulary of the jurist Martino da Fano, is the depositary of a peculiar ability to discernere: «discretus, in intelligendo, disquirendo et componendo».